Queering John of the Cross: Sanjuanist Contributions to the Fight against Phobias towards Queer People - Anderson Fabian Santos Meza (Religions, 2024)
This article aims to approach Sanjuanist mysticism from a queer perspective. It is not a monolithic apology to queer people, nor a treatise on mystical interpretation, but an effort to recognize and validate the spiritual experience of LGBTIQ+ people. It takes some mystical passages from St. John of the Cross that help to read the experience of queer life in a mystical key. With this, the potential of mysticism to combat those phobic, segregating, and unjust ideologies that mistreat so many people because of their sexual orientation and gender identity dissidence is manifested. Although it is problematic, talking about this is an act of epistemic, sociocultural, and religious justice.